2021
DOI: 10.1101/mcs.a006137
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive SLC30A9 variants in a Proband with a Cerebro-Renal Syndrome and No Parental Consanguinity

Abstract: An SLC30A9 associated cerebro renal syndrome was first reported in consanguineous Bedouin kindred by Perez et al in 2017. While the function of the gene has not yet been fully elucidated, it may be implicated in Wnt signaling, nuclear regulation, as well as cell and mitochondrial zinc regulation. In this research report, we present a female proband with two distinct, inherited autosomal recessive loss of function SLC30A9 variants from unrelated parents. To our knowledge, this is the first reported case of a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…Only 1 of our probands (F2) has definite renal dysfunction, although 1 member of family F1 is also known to renal services, and none currently have hypertension or hyperkalemia. Hearing impairment was not found in any of Perez et al's index kindred 2 but was found in the Kleyner et al proband,3 and in at least 3 of the individuals we report here (F1(II-1), F2, and F4): family 3 has not had a detailed audiologic assessment.SLC30A9 encodes ZnT-9, a ubiquitously expressed transmembrane protein, which is known to play a role as a zinc transporter. Perez et al, in the same study in which they report on the disease, offer immunofluorescence-based evidence that the protein colocalizes with cytosolic vesicles and especially the endoplasmic reticulum.…”
contrasting
confidence: 45%
See 4 more Smart Citations
“…Only 1 of our probands (F2) has definite renal dysfunction, although 1 member of family F1 is also known to renal services, and none currently have hypertension or hyperkalemia. Hearing impairment was not found in any of Perez et al's index kindred 2 but was found in the Kleyner et al proband,3 and in at least 3 of the individuals we report here (F1(II-1), F2, and F4): family 3 has not had a detailed audiologic assessment.SLC30A9 encodes ZnT-9, a ubiquitously expressed transmembrane protein, which is known to play a role as a zinc transporter. Perez et al, in the same study in which they report on the disease, offer immunofluorescence-based evidence that the protein colocalizes with cytosolic vesicles and especially the endoplasmic reticulum.…”
contrasting
confidence: 45%
“…Only one of our probands (F2) has definite renal dysfunction, although one member of Family F1 is also known to renal services, and none currently have hypertension or hyperkalaemia. w P ' index kindred (2) but was found in the Kleyner et al proband (3), and in at least three of the individuals we report here (F1(II-1), F2 and F4): Family 3 has not had a detailed audiological assessment.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations